Peculiarities of the use of enteral nutrition in patients with severe acute pancreatitis - Kolosovуch I. V.; Hanol, I. V. (General Surgery, 2023)
In the general structure of the disease, severe acute pancreatitis occurs in 20% of cases, requires treatment in the intensive care unit, and is accompanied by a high risk of complications (up to 50%) and death (40—70%). In turn, early use of enteral nutrition in patients with severe acute pancreatitis significantly improves the condition of the intestinal wall and the course of the disease as a whole, reducing the number of complications and mortality. Objective — to determine the timeframe for the restoration of intestinal absorptive function as one of the main criteria for the start of enteral nutrition in patients with severe acute pancreatitis and to improve the results of comprehensive treatment of patients by preventing its complications. Materials and methods. The results of the evaluation and treatment of 67 patients with severe acute pancreatitis served as the basis for the study. Patients were divided into two groups depending on the specifics of the selected treatment strategies: a comparison group of 33 patients receiving standard enteral nutrition and a main group of 34 patients receiving standard enteral nutrition with the inclusion of antiflatulants in the mixture. Before the start of tube feeding, a test using unmetabolized disaccharides (lactulose/mannitol) and a sample containing a 3% potassium iodide solution was conducted to determine the timeframe for the restoration of intestinal absorptive function. Results. Іn 70.6% of patients in the main group and 69.7% of patients in the comparison group, the restoration of intestinal absorptive function was registered only after 48 hours from the beginning of treatment. After 7 and 14 days of enteral nutrition, a significant difference was obtained between total protein, albumin, cholesterol and serum K+ (p<0.05). Аfter 7 days of treatment, there was a significantly lower incidence of intestinal complications in patients of the main group by 21.5% (χ2=4.88, 95% CI 2.3—39.5, p=0.03). Conclusions. The method, which uses a 3% potassium iodide solution, is quick and informative for determining the restoration of intestinal absorptive function in patients with severe acute pancreatitis. The inclusion of antiflatulants in the composition for enteral nutrition improved the laboratory parameters of blood serum and reduced the incidence of intestinal complications by 7 days and the duration of multiorgan failure from 11.5±1.8 days to 10.5±1.9 days (p=0.04).